GENETIC ANAlYSIS OF EAST AND WEST COAST POPUlATIONS OF PENAEUS MONODOIV INDIA BASED ON RANDOM AMPliFIED POlYMORPHIC DNA - Mishra, Prem Sagar; Lakra, W S; Chaudhari, Aparna (Journal of Indian Fisheries Association, 2008)
The east and west coast populations of wild Penaeus monodon in India were geneticai~ycharacterized by RAPD analysis using six highly polymorphic primers reported earlier. The av.eragegenetic similar~ties within populations, based on profiles generated by all the six primers, were0.828 and 0.851 for the east and west coast populations, respectively, values with individualprimers ranging from 0.744 to 0.889. The average genetic similarity between populations acrossail the primers was 0.774. The number of bands found to be polymorphic were 38 (51.35%}(50.68%) in the east and west coast populations, respectively. Primer 5 yielded tne highest ieveupolymorphism (63.63%) in the east coast population whereas primer 3 yielded the lowest level ofpolymorphism (36.36%) in the west coast population. The study reveals the existence of genetu•tvariation in P. monodon stocks providing scope for genetic improvement through selectilvebreeding. It also provides baseline data for future work on population structure analysis o'J iP,monodon.Key words: RAPD, P. monodon, genetic diversity, polymorphism.INTRODUCTIONOne of the fastest growingaquaculture production